Contrasting Responses of Plastid Terminal Oxidase Activity Under Salt Stress in Two C4 Species With Different Salt Tolerance - Essemine, Jemaa; Lyu, Ming-Ju Amy; Qu, Mingnan; Perveen, Shahnaz; Khan, Naveed; Song, Qingfeng; Chen, Genyun; Zhu, Xin-Guang (Frontiers in Plant Science, 2020)
The present study reveals contrasting responses of photosynthesis to salt stress in two C4 species: a glycophyte Setaria viridis (SV) and a halophyte Spartina alterniflora (SA). Specifically, the effect of short-term salt stress treatment on the photosynthetic CO2 uptake and electron transport were investigated in SV and its salt-tolerant close relative SA. In this experiment, at the beginning, plants were grown in soil then were exposed to salt stress under hydroponic conditions for two weeks. SV demonstrated a much higher susceptibility to salt stress than SA; while, SV was incapable to survive subjected to about 100 mM, SA can tolerate salt concentrations up to 550 mM with slight effect on photosynthetic CO2 uptake rates and electrons transport chain conductance (gETC). Regardless the oxygen concentration used, our results show an enhancement in the P700 oxidation with increasing O2 concentration for SV following NaCl treatment and almost no change for SA. We also observed an activation of the cyclic NDH-dependent pathway in SV by about 2.36 times upon exposure to 50 mM NaCl for 12 days (d); however, its activity in SA drops by about 25% compared to the control without salt treatment. Using PTOX inhibitor (n-PG) and that of the Qo-binding site of Cytb6/f (DBMIB), at two O2 levels (2% and 21%), to restrict electrons flow towards PSI, we successfully revealed the presence of a possible PTOX activity under salt stress for SA but not for SV. However, by q-PCR and western-blot analysis, we showed an increase in PTOX amount by about 3~4 times for SA under salt stress but not or very less for SV. Overall, this study provides strong proof for the existence of PTOX as an alternative electron pathway in C4 species (SA), which might play more than a photoprotective role under salt stress.